Test and Analysis of Performance of Flat Single-axis Photovoltaic Tracking Bracket Multi-point Drive Rotary Reducers - Ma Tao; Li Wei; Chen Xuehui; Gao Ting; Li Wei; Tang Xing (Jixie chuandong)
A new type of rotary reducer is urgently needed in engineering to improve the low efficiency of single point drive operation for flat single axis photovoltaic tracking brackets, in order to adapt to complex environments and reduce costs. For this purpose, a cylindrical worm helical gear toroidal worm multi-point drive rotary reducer was designed, and performance testing and analysis were conducted. Firstly, the installation position and transmission mechanism of the multi-point drive rotary reducer were analyzed and compared with that of the single point drive. Secondly, the performance of the rotary reducer under rated output torque and overturning torque was numerically simulated using Romax software, and a comprehensive performance testing platform for the rotary reducer was built to test the transmission performance of the prototype under rated output torque and overturning torque. The results show that multi-point drive can withstand larger loads compared to single point drive, and the overall stability of the tracking bracket is stronger; the larger the rated output torque value, the greater the stress value of the worm gear; the overall stress value and deformation of the secondary transmission mechanism under the overturning torque meet the actual working condition requirements; the test does not cause significant damage inside the reducer, and the simulation and test results are in good agreement. The design of the rotary reducer meets the practical working characteristics of the flat single axis photovoltaic tracking bracket under harsh working conditions, and can provide theoretical reference and support for improving the photovoltaic conversion efficiency construction of photovoltaic power stations.